A Translation and Cross-cultural Adaptation of the Flodén Attitudes Toward Organ Donor Advocacy Instrument (ATODAI) into Greek. - Kalli, Antonia; Andrea-Apostolidou, Stavroula; Leonidou, Maria; Lamnisos, Dimitris (Nursing Care & Research / Nosileia kai Ereuna)
INTRODUCTION: The care of specialist nurses is the key to successful donor management in the critical care setting since their actions and specific behavior is significantly associated with authorization or decline of organ donation. PURPOSE: To translate, adapt and establish the psychometric properties of the Greek version of the Flodén ATODAI (Attitudes Toward Organ Donor Advocacy Instrument) in terms of validity and reliability. MATERIAL-METHOD: A multi-step approach were used: Initial translation; Back-translation; Review and synthesis of these translations; Expert panel (N=7) rated the instrument for content validity index on each item (I-CVI) and on the instrument (S-CVI); Reliability testing with test and retest was analyzed with the appropriate correlation coefficient (r) and Cronbach's alpha coefficient (a) (N= 37); Delphi technique procedure, with a panel of N=10. RESULTS: The content validity index was calculated on each item as well as on the entire 46-item Flodén ATODAI [Greek version]. I-CVI ranged from .29 to 1.0, mean .95 and the S-CVI (averaging) was .95.r = 0.470 -- 1,000, all having a significance value of P < .01. In total, 45 of the items had a moderate or higher strength of correlation. Homogeneity reliability was estimated by a and was calculated for the 40 items with r >.70. The overall α was .96. The Delphi technique procedure resulted in adjustments after both round I and round II, involved emphasizing the core of the items by re-wording, and establishing that consensus was achieved. CONCLUSION: Undertaking this multi-step approach has effectively ensured that the cross-cultural adaptation procedure resulted in a stronger instrument for valid and reliable measurements.